The effects of reactants ratios, reaction temperatures and times on Maillard reaction products of the L-ascorbic acid/L-glutamic acid system - ZHOU,Yong-Yan (2016)
Abstract The transformation law of the Maillard reaction products with three different reactants ratios - equimolar reactants, excess L-glutamic acid and excess L-ascorbic acid reaction respectively, five different temperatures, and different time conditions for the L-ascorbic acid / L-glutamic acid system were investigated. Results showed that, the increase of the reaction time and temperature led to the increase of the browning products, uncoloured intermediate products, as well as aroma compounds. Compared with the equimolar reaction system, the excess L-ascorbic acid reaction system produced more browning products and uncoloured intermediate products, while the aroma compounds production remained the same. In the excess L-glutamic acid system, the uncoloured intermediate products increased slightly, the browning products remained the same, while the aroma compounds increased.